Gender, Insecurity and Access to Primary Health Care in Ekiti State - Ojuawo Olakunle Olaniyi; Aluko Olanrewaju (International Journal of Innovative Science and Research Technology, 2026)
Access to primary healthcare remains central to achieving Universal Health Coverage; however, gender inequalities and emerging security challenges increasingly constrain healthcare utilisation in many developing countries. This study examined the relationship between gender, insecurity, and access to primary healthcare in Ekiti State, Nigeria. Specifically, the study investigated the influence of insecurity on primary healthcare access, analysed the gender dimensions of healthcare utilisation, and explored how insecurity differently affects men's and women's access to healthcare services. The study adopted a qualitative research design based on documentary analysis. Data were obtained from peer-reviewed journal articles, government publications, policy documents, and reports of reputable national and international organisations published mainly between 2020 and 2026. The data were analysed using thematic content analysis. The findings revealed that insecurity, including security breaches at health facilities, kidnapping incidents, and fear of travelling, particularly at night, has emerged as an important barrier to healthcare utilisation. The study further found that women experience greater obstacles to accessing primary healthcare due to financial dependence, restricted mobility, limited decision-making power, and caregiving responsibilities, while men are constrained by cultural norms surrounding masculinity and delayed health-seeking behaviour. The intersection of gender and insecurity therefore creates unequal healthcare experiences across population groups. The study concludes that strengthening primary healthcare in Ekiti State requires policies that integrate gender-responsive interventions with security-sensitive healthcare planning. It recommends improving security infrastructure at health facilities, expanding financial protection mechanisms, promoting male involvement in maternal healthcare, strengthening the health workforce, and mainstreaming security risk assessments into health sector planning to enhance equitable access to primary healthcare.